If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -25b + 5 = 19 Reorder the terms: 5 + -25b = 19 Solving 5 + -25b = 19 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -25b = 19 + -5 Combine like terms: 5 + -5 = 0 0 + -25b = 19 + -5 -25b = 19 + -5 Combine like terms: 19 + -5 = 14 -25b = 14 Divide each side by '-25'. b = -0.56 Simplifying b = -0.56
| 0.01(x-8)(x-3)(x+8)(x+3)=5 | | factorx^2-20x+100-y^2= | | 17(7c-1)-12=117c+17 | | x^4-8x+18=0 | | 6,435/8= | | 8-2x=13+3x | | -14n+12=-12n-12 | | 6(0.5)=Y(.25) | | 6+1=438 | | -3+9=17x-4-16x | | 3(6x-1)=-19x | | 4(w-8)=8+3w | | 9y-14y=-24-31 | | -11-(-42)=x/6 | | 4-c=20 | | 76(-2x-3)=.19x+6 | | 4y^8+15y^4+11= | | 16x^3+24x=-9 | | 16x^3+24x+9=0 | | (29-51x^3)/x | | 5x*5x=40 | | 4x-2x+7x=23 | | 1x+3=9y | | 15y+42=67y*15 | | 2/5x-10 | | 8+7=-3(3x-5) | | 2/3x-0.4y=2 | | x+23=7x+47 | | 2x-2/3+1/3=4 | | 8-11=5 | | 4(7x+10x)=3(9x-5)+20 | | 1+(3*2)=x |